2022
DOI: 10.3390/plants11040495
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling of Allium subhirsutum L. Aqueous Extract with Antioxidant, Antimicrobial, Antibiofilm, and Anti-Quorum Sensing Properties: In Vitro and In Silico Studies

Abstract: The present study was the first to evaluate the phytochemical composition, antioxidant, antimicrobial, antibiofilm, and anti-quorum sensing potential of Allium subhirsutum L. (hairy garlic) aqueous extract through in vitro and in silico studies. The phytochemical profile revealed the presence of saponins, terpenes, flavonols/flavonones, flavonoids, and fatty acids, particularly with flavonoids (231 ± 0.022 mg QE/g extract), tannins (159 ± 0.006 mg TAE/g extract), and phenols (4 ± 0.004 mg GAE/g extract). Gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…The available literature demonstrated that diallyl sulfides exhibited promising antimicrobial activity [ 37 , 39 , 40 , 41 , 42 ]. Our results confirmed that, although allicin contributes to the antibacterial properties of hydroalcoholic extracts of garlic [ 43 , 44 ], it could exhibit a breaking effect on the biofilm inhibitory action of the A. sativum EOs.…”
Section: Resultssupporting
confidence: 86%
“…The available literature demonstrated that diallyl sulfides exhibited promising antimicrobial activity [ 37 , 39 , 40 , 41 , 42 ]. Our results confirmed that, although allicin contributes to the antibacterial properties of hydroalcoholic extracts of garlic [ 43 , 44 ], it could exhibit a breaking effect on the biofilm inhibitory action of the A. sativum EOs.…”
Section: Resultssupporting
confidence: 86%
“…The effect of T. musilii methanolic extract to inhibit the biofilm formation on 96-well plates by S. aureus ATCC 25923, E. faecalis ATCC 19433, E. coli ATCC 25922, P. aeruginosa ATCC 27853, Salmonella typhimurium ATCC 14028, L. monocytogenes ATCC 7644, and C. albicans ATCC 10,239 was tested by crystal violet technique [ 35 ]. For the experiment, 50 µL of an overnight-grown micro-organism culture and tryptone broth was prepared at different concentrations of T. musilii extracts (1, 1/2, 1/4, 1/8, and 1/16 MIC concentration value).…”
Section: Methodsmentioning
confidence: 99%
“…190 Advanced spectroscopic analysis showed that different bioactive compounds (eg, flavonoids, phenols, terpenes, and tannins) contribute to the versatile biological action of natural constituents, including the antibiofilm effect. [189][190][191][192] In conclusion, bacteria alter their gene expression by sensing the levels of molecules depending on the external environment, thus affecting biofilm production and other virulence factors. 193 Phytochemicals can regulate QS and, as a result, control biofilm-caused infections by controlling bacterial gene expression.…”
Section: Natural Products (Phytochemicals)mentioning
confidence: 99%
“…For example, Allium subhirsutum L. (hairy garlic) proved to have antibiofilm, anti-quorum-sensing, and antibacterial activity against different bacterial and fungal isolates. 189 Eruca sativa Miller was tested against numerous food-borne pathogens for their antibacterial and antibiofilm activity and demonstrated reduced bacterial density within the biofilm community and a disturbed integrity of the biofilms by interfering with exopolysaccharides synthesis. 190 Also, the molecular analysis found that E. sativa phytochemicals fused with multiple adhesion proteins associated with biofilm formation, causing compromised biofilm formation.…”
Section: Innovative Approaches To Curb Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation